Accessibility, diversity, equity and inclusion in the cultural sector : initiatives and lessons learned from real-life cases - Bérubé, Julie; Dioh, Marie-Laure; Cuyler, Antonio C. (Emerald Publishing Limited, 2024)
Though accessibility, diversity, equity and inclusion (ADEI) are currently at the heart of many debates and social concerns around the world, few academic studies have explored real world ADEI initiatives in the creative sector. Accessibility, Diversity, Equity and Inclusion in the Cultural Sector unpacks real-life initiatives and experiences to reveal how those working in these sectors integrate ADEI into their management practices. Acknowledging the importance of geographic and disciplinary contexts in approaching ADEI issues, chapters offer a broad representation of art disciplines, including the performing arts, music, visual arts and events industries, taking as examples opera houses, orchestras, theaters, arts museums, festivals, federal cultural administrations and even the Super Bowl. Equipping researchers and practitioners to make quick connections between research and practical settings, the authors present case studies from across the globe, including Colombia, Canada, the US, South Africa, Chile, Haiti, Australia and Taiwan, to provide a holistic view of how ADEI issues are addressed across different regions. Advocating for the immersion of ADEI practices into the heart of art organizations, Accessibility, Diversity, Equity and Inclusion in the Cultural Sector links theory, practice and context as a way to further enrich cultural communities and wield the deeply human power of art for real human impact.
Keywords: Multiculturalism.; Arts.; Diversity in the workplace.; Business & Economics -- Organizational Behavior.; Diversity, equality and inclusion in the workplace.; Organizational theory and behaviour.; elektronické knihy; electronic books